An update on efficacy and safety considerations for the latest drugs used to treat irritable bowel syndrome. (2nd July 2020) - Mousavi, Taraneh; Nikfar, Shekoufeh; Abdollahi, Mohammad
ABSTRACT: Introduction: Irritable bowel syndrome (IBS), globally affecting 11.2% of the population and imposing a direct annual cost of $1.7bn-$10bn in the US, is one of the today's major therapeutic challenges. Therefore, there is urgent need to address this issue through reviewing the tolerability and efficacy of available medications. Areas covered: Over the past decade, related experiments were cited through Clinicaltrials.gov, PubMed, WHO ICTRP, and Cochrane library. Pharmacological parameters of approved medications available in the USFDA, EMA, TGA and PMDA were also stated. Expert opinion: Anti-spasmodics are used as the first-line treatment in pain-predominant IBS and IBS-D, among which calcium channel blockers and neurokinin-type 2 receptor antagonists seem to replace anti-cholinergic drugs. As second-line treatments, rifaximin is considered to be the best for IBS-D though it has lower efficacy than alosetron and eluxadoline. For IBS-C, linaclotide is the most effective and the safest second-line therapy, following laxatives/fibers, which may be replaced by tenapanor, in the future. When moderate to severe IBS is associated with severe pain or comorbid psychological disorders, gut-brain neuromodulators could also be prescribed. Regarding all this, there is still a paramount need to conduct careful clinical studies on efficacy, safety and cost-effectiveness of current approved and non-approved treatments.